On organizing: an interview with James G. March - Jiyang Dong; James G. March; Maciej Workiewicz (Journal of Organization Design, 2017)
In this interview with Professor James G. March, we focused on the key insights stemming from his work, with a special emphasis on the lessons for organization science and organization design. We discussed the major ideas and theories that he and his coauthors generated over the several decades as well as asked him about his views on the role of management research and business academia in general. The interview was conducted in September 2013 in Stanford, CA, and updated in August 2017 with a postscript from James G. March directed to the organization design community.
Keywords: 650; Interview; Behavioral theory of the firm; Carnegie school; Organization design